Comprehensive Review on Role of H. pylori in Stomach Ulcer and Detect Eradication after Giving Therapies - Shahid, Hanan; Salman, Muhammad; Nasir, Khadeeja (Indus Journal of Bioscience Research, 2025)
Peptic ulcer disease (PUD) remains a significant global health concern, primarily attributed to infection with Helicobacter pylori (H. pylori), a Gram-negative, spiral-shaped bacterium. This review examines the pathogenic role of H. pylori in ulcer formation and assesses current eradication therapies. The bacterium colonizes the gastric mucosa by producing urease to neutralize gastric acid and releasing virulence factors that compromise the mucosal barrier, leading to chronic inflammation and ulceration. Diagnostic methods for H. pylori include non-invasive tests—such as the urea breath test and stool antigen test—and invasive procedures like endoscopic biopsy with histological analysis. Standard treatment involves triple or quadruple therapy using a combination of antibiotics and proton pump inhibitors (PPIs). However, rising antibiotic resistance has diminished the effectiveness of these regimens, prompting the exploration of alternative strategies, including tailored therapy and novel antimicrobial agents. Globally, H. pylori prevalence varies, with higher infection rates in developing regions due to inadequate sanitation and limited access to healthcare. In Pakistan, roughly one-third of gastric ulcer cases are linked to H. pylori, paralleling the global adult infection rate of approximately 45%. Despite available treatments, recurrence and complications persist, underscoring the need for personalized care and improved therapeutic protocols. This review emphasizes the importance of early diagnosis, appropriate antibiotic use, and ongoing research into new treatments, including vaccines. Advancements in these areas are vital for reducing the burden of H. pylori-related gastrointestinal diseases.